Microfinance and poverty reduction - Johnson, Susan; Rogaly, Ben.; Oxfam (Oxford, United Kingdom : Oxfam : ACTIONAID, 1997)
This book focuses on microfinance and only briefly discusses its relationship to other development activities
Includes bibliographical references (p. 128-134).
osa 08/15/13
Loans
Keywords: Microfinance; Poor -- Developing countries; Poverty -- Developing countries; Non-governmental organizations -- Developing countries; Sustainable development -- Developing countries; Financial institutions -- Developing countries